(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Preeclampsia is a serious problem that leads to many deaths of both mothers and babies all over the world, particularly in developing countries. This condition specially related to pregnancy. Preeclampsia is caused by a number of factors, including problems with the placenta, imbalances in the body's natural processes, and damage to blood vessels. Objective: To compare both perinatal and maternal outcomes among preeclampsia patients with advanced maternal age (AMA) and those with normal reproductive age group (RA). Study design: Analytical cross-sectional study. Place and Duration: This study was conducted at Hayatabad Medical Complex/Medical and Teaching Institute Peshawar KPK from Jan 2020 to Dec 2022. Methodology: Overall, a total of 120 women were enrolled in this research. All of the women involved in this research were diagnosed with preeclampsia. The data for all participants was collected from the medical records of the women that were enrolled in this research. All of the 120 women were divided into two groups according to their maternal ages. One group contained women with maternal age 35 years or above. This group was called Advanced Maternal Age (AMA). The other group contained women with normal reproductive age which is from 20 years to 34 years of age. Results: There were 35 women in the advanced maternal age group and 85 women in the normal reproductive age group. The poor perinatal and maternal outcomes were more in the advanced age group. Females in the advanced maternal age group had a higher incidence of C-sections, postpartum hemorrhage, pulmonary edema, visual impairment, birth asphyxia and intrauterine growth restriction. Conclusion: In conclusion, poor perinatal and maternal outcomes are caused by advanced maternal age in pregnant women presenting with preeclampsia.